Analisis Perbandingan Performa Protokol Routing OSPF, IGRP dan EIGRP pada Topologi Mesh dan Tree - Enggar Saka Dirgantara; Rakhmadhany Primananda; Widhi Yahya (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The Internet is a set of interconnected Autonomous Systems (AS). Autonomous systems connect with other autonomous systems with different routing policies. Each routing protocol has a different character, need to do research using routing protocol OSPF, IGRP and EIGRP on mesh and tree topologi. This research is intended to find out the best routing protocol in each topologi. This research performs data transmission using TCP and UDP protocol. Data packets that like to use TCP protocol are HTTP and UDP protocol is VoIP. Testing is done by way of several routers into mesh and tree topologi, with the number of routers 16, 32 and 64.The simulation shows on the mesh topologi and topologi tree, EIGRP has the fastest convergence time of other routing protocols. OSPF is very well used in tree topologi compared to other routing protocols. EIGRP occurs stuck in active in the topologi tree, so it has poor performance. EIGRP has the best performance in mesh topologi compared to other routing protocols. But if the mesh topologi is connected with several different types of links there will be bottle neck, larger than other routing protocols.